Pengaruh Modal Dan Lokasi Terhadap Pendapatan Pedagang Di Pasar Tradisional Tac Kota Jambi - Efni Anita; Ahmad Syahrizal; Setiyani Setiyani (JOURNAL SAINS STUDENT RESEARCH, 2023)
This thesis is entitled The Influence of Capital and Location on Traders' Income in the Tac Traditional Market, Jambi City. This research aims to determine the influence of capital and location simultaneously and partially on the income of TAC traditional market traders. The method used in this research is descriptive quantitative, where in collecting data researchers use observation, interviews, questionnaires and documentation methods. The number of samples in this study was 35 traders, and the total quota sampling technique was used, as a technique to determine samples from the population that have certain characteristics to the desired number (quota). The research results show that capital and location have a significant positive effect on income. The results of the T test on capital value tcount > ttable, namely 3.148 > 2.035, which means Ha is accepted, meaning capital has a significant effect on trader income. The T test at the location has a value of tcount > ttable, namely 3.087 > 2.035, which means that Ha is accepted, meaning that location has a significant effect on the trader's income. Meanwhile, the results of the F test show that the value of fcount > ftable is 21.630 > 3.28. It can be concluded that Ha is accepted, which means that the capital and location variables together or simultaneously influence the trader's income. The coefficient of determination (R Square) value obtained was 0.575, indicating that 57.5% of the trader's income variable could be explained by the two independent variables. Meanwhile, the remaining 42.5% is explained by other variables not examined in this study. Based on data analysis in this research, these variables are valid and reliable. When testing classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occur.